Tugendhat's Idea of Truth. (15th January 2016) - Skirke, Christian
Abstract: This paper argues that Tugendhat's critique of Heidegger's existential conception of truth as disclosedness is usually misunderstood. The main claim of this paper is that Tugendhat insists against Heidegger on certain conventional features of truth such as conformity of the law of non‐contradiction, not because he adheres to an ideal of truth as correctness; rather, he proposes an alternative existential conception of truth in terms of an active, critical or self‐critical, engagement with untruth. Various recent objections to Tugendhat's critique of Heidegger are discussed against the background of his alternative and are rejected. The paper concludes by outlining several challenges to Tugendhat's alternative existential conception of truth.